أثر استرايجيات إدارة الانطباع التنظيمي على سلوكيات الصوت الوظيفي -دراسة ميدانية المؤسسة الوطنية للدهن وحدة سوق اهراس - شاديةجلابي (My University, 2022)
This study aimed to know the level of organizational impression management strategies in the National Oil Corporation in general and the targeted sample in particular, and to know the degree of their impact on the level of job voice behaviors, by focusing on the three dimensions of organizational impression management strategies (self-reinforcement strategy, adulation strategy, strategy Threat), and in order to achieve the goal of the study and test the validity of its hypotheses, the questionnaire was relied on as a main tool for collecting the necessary data, which was distributed to a random sample of 35 individuals from the total employees of the National Oil Corporation ENAP, SOUK-Ahras . After collecting the forms, we used a set of appropriate statistical methods (based on the SPSS V26 program), the results of the normal distribution, the reliability coefficient, the internal validity, the arithmetic means, the standard deviations, the relative importance, the correlation matrix and the regression coefficient were extracted. And one of the most important results we have reached is the presence of a statistically significant effect of the organizational impression management strategies on the job voice behaviors in the ENAP organization at the level of significance (0.05), which confirmed that the organization pays attention to the concept of organizational impression management strategies through its practiced voice behaviors. This has had a significant and positive impact on its reputation and image. ................................................................. هدفت هذه الدراسة إلى معرفة مستوى استراتيجيات إدارة الانطباع التنظيمي في المؤسسة الوطنية للدهن بشكل عام و العينة المستهدفة بشكل خاص و معرفة درجة تأثيرها في مستوى سلوكيات الصوت الوظيفي، من خلال التركيز على الأبعاد الثلاثة لاستراتيجيات إدارة الانطباع التنظيمي ) استراتيجية التعزيز الذاتي، إستراتيجية التزلف، إستراتيجية التهديد (، و من اجل تحقيق هدف الدراسة و اختبار صحة فرضياته تم الاعتماد على الاستبيان كأداة رئيسية لجمع البيانات اللازمة، التي تم توزيعها على عينة عشوائية مكونة من 53 فردا من جملة وحدة سوق أىراس. ENAP الموظفين بالمؤسسة الوطنية للدهن بعد جمع الاستمارات قمنا باستخدام مجموعة من الأساليب الإحصائية الملائمة ) الاعتماد على برنامج تم استخراج النتائج الخاصة بالتوزيع الطبيعي، و معامل الثبات و الصدق الداخلي، و الأوساط ،)SPSS V26 الحسابية، و الانحرافات المعيارية، و الأهمية النسبية، و مصفوفة الارتباط و معامل الانحدار، و من أهم النتائج التي توصلنا إليها وجود اثر ذو دلالة إحصائية لاستراتيجيات إدارة الانطباع التنظيمي على سلوكيات الصوت الوظيفي عند مستوى دلالة ) 3...(، و الذي أكد على أن المؤسسة تولي اهتماما لمفهوم ENAP في مؤسسة استراتيجيات إدارة الانطباع التنظيمي من خلال سلوكيات الصوت الممارسة لديها لذلك من تأثير كبير و ايجابي على سمعتها و صورتها.